Viral Immune signatures from cerebrospinal fluid extracellular vesicles and particles in HAM and other chronic neurological diseases - Pleet, Michelle L.; Welsh, Joshua A.; Stack, Emily H.; Cook, Sean; Johnson, Dove-Anna; Killingsworth, Bryce; Traynor, Tim; Clauze, Annaliese; Hughes, Randall; Monaco, Maria Chiara; Ngouth, Nyater; Ohayon, Joan; et al. (Frontiers in Immunology, 2023)
Background and Objectives: Extracellular vesicles and particles (EVPs) are released from virtually all cell types, and may package many inflammatory factors and, in the case of infection, viral components. As such, EVPs can play not only a direct role in the development and progression of disease but can also be used as biomarkers. Here, we characterized immune signatures of EVPs from the cerebrospinal fluid (CSF) of individuals with HTLV-1-associated myelopathy (HAM), other chronic neurologic diseases, and healthy volunteers (HVs) to determine potential indicators of viral involvement and mechanisms of disease. Methods: We analyzed the EVPs from the CSF of HVs, individuals with HAM, HTLV-1-infected asymptomatic carriers (ACs), and from patients with a variety of chronic neurologic diseases of both known viral and non-viral etiologies to investigate the surface repertoires of CSF EVPs during disease. Results: Significant increases in CD8+ and CD2+ EVPs were found in HAM patient CSF samples compared to other clinical groups (p = 0.0002 and p = 0.0003 compared to HVs, respectively, and p = 0.001 and p = 0.0228 compared to MS, respectively), consistent with the immunopathologically-mediated disease associated with CD8+ T-cells in the central nervous system (CNS) of HAM patients. Furthermore, CD8+ (p < 0.0001), CD2+ (p < 0.0001), CD44+ (p = 0.0176), and CD40+ (p = 0.0413) EVP signals were significantly increased in the CSF from individuals with viral infections compared to those without. Discussion: These data suggest that CD8+ and CD2+ CSF EVPs may be important as: 1) potential biomarkers and indicators of disease pathways for viral-mediated neurological diseases, particularly HAM, and 2) as possible meditators of the disease process in infected individuals.